Woodsmoke and diesel exhaust: Distinct transcriptomic profiles in the human airway epithelium - Ryan D. Huff; Christopher F. Rider; Theodora Lo; Kristen I. Hardy; Nataly El-Bittar; Min Hyung Ryu; Chris Carlsten; Emilia L. Lim (Ecotoxicology and Environmental Safety, 2025)
Climate change is increasing the frequency and severity of wildfires globally, causing significant woodsmoke (WS) emissions. Vehicles emit sizable amounts of toxic traffic-related air pollution (TRAP), for which diesel exhaust (DE) is a model. Both WS and DE contain particulate matter < 2.5 microns (PM2.5), which deeply penetrates the lungs causing respiratory epithelial inflammation that drives health effects. Regulations focus on PM2.5 concentration, despite emerging research that highlights how composition mediates health effects. As WS and DE are compositionally distinct, we conducted the first head-to-head comparison of effects on the transcriptomes of air-liquid interface cultured primary human bronchial epithelial cells (HBEC). Differentiated donor-matched HBEC transwells were exposed for 2-hours to filtered air (FA; control), or WS (furnace tube burning pine) or DE (Hatz 1B30E generator) both diluted to 300 µg/m3 of PM2.5. WS had higher ultrafine PM, whereas DE exposure contained significantly higher NO2, CO, and O3. RNA sequencing showed that WS exposure resulted in 159 (↑50, ↓109) differentially expressed genes, while DE modulated 439 (↑264, ↓175) compared to FA exposure. WS was associated with small ribosomal subunit and cytochrome complex related genes, while DE exposure was associated with HIF-1 signaling, respiratory chain complex and interferon alpha/beta signaling/ISG15-protein conjugation, suggesting how TRAP exposure may enhance infection risk. We also analyzed exposure effects on protein immune-mediators. We demonstrate that two major air pollution sources modulate different genes and pathways in HBECs, with minimal overlap. This informs the debate regarding the regulatory focus on concentration and assumptions that similar concentrations of air pollution have indistinct effects.